2018
DOI: 10.1177/1469787418798517
|View full text |Cite
|
Sign up to set email alerts
|

Study-related exhaustion: First-year students’ use of self-regulation of learning and peer learning and perceived value of peer support

Abstract: This study examines the profiles of self-regulation of learning, peer learning and peer support among students. The study investigates whether the profiles differ in terms of reported study-related exhaustion. Students completed a questionnaire regarding their use of self-regulation of learning and peer learning and perceived peer support and study-related exhaustion. Four different student profiles were found. The profiles differed in terms of self-reported study-related exhaustion. Self-regulated students wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 45 publications
4
24
0
6
Order By: Relevance
“…In the obtained results, it is striking that students do not use closeness with peers and teachers as the main strategy to access information, making little use of peer learning [120,121].…”
Section: Discussionmentioning
confidence: 96%
“…In the obtained results, it is striking that students do not use closeness with peers and teachers as the main strategy to access information, making little use of peer learning [120,121].…”
Section: Discussionmentioning
confidence: 96%
“…Individuals tend to learn more when they learn with others than when they learn alone (Michael, 2006). According to Räisänen et al (2020), in peer learning, students learn through the interaction with each other. In several studies, groupwork has been found to augment academic achievement (Gull & Shehzad, 2015;McMaster & Fuchs, 2002;Nichols, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing range of courses offered to students with diverse backgrounds and levels of preparedness has resulted in intense teaching challenges at institutions of higher learning (Northedge, 2003). For the majority of students, including those who are successful, the transition to university can be both a great and difficult encounter (Räisänen et al, 2020). In addition to the incorporation of remedial support to struggling students within institutions and teaching programs to address the above-mentioned challenges, there has been a call for a radical shift from the teacher-centered approach of teaching to the student-centered teaching approach (Dema & Tshering, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We are often not aware of the individual backgrounds of the students we are teaching as to their independence and skill set with regard to learning and studying. Räisänen et al (2018) notes that the transition to university is challenging for many students. There is evidence that the first year is a crucial time for the students.…”
Section: Emergent Srlmentioning
confidence: 99%